RISK MANAGEMENT OF ALLERGENIC FOOD INGREDIENTS IN HOSPITALITY - Popov-Raljić, Jovanka; Aleksić, Milica; Janković, Vesna; Blešić, Ivana; Ivkov, Milan (Economics of Agriculture, 2017)
Food allergens have appeared in the last two decades as a concealed form of threat which signifcantly endangers public health, and their labelling on food products, drinks, and non pre-packed gastro-products is clearly defned with legal regulations. In practice, the chemical risk management is faced with several unexpected problems. Some of them are declarations or statements about allergenic ingredients, where a nutritional allergen that the food contains is labelled with an unusual name, or similar products from different manufacturers where one is safe and the other contains allergens. A hospitality facility which deals with production and distribution of unpackaged foods should, in addition to a developed HACCP concept and standardized recipes for food preparation, prepare a detailed, precise, and clearly defned plan for management of chemical risks.